Better Mentorship, Better Student Experience: An Introduction to Mentorship: AEC799/WC460, 5/2024 - Barry, Debra M.; Nesbitt, Heather; McAuslane, Heather (EDIS, 2024)
This initial article in the Better Mentorship, Better Student Experience series provides faculty and students with a basic understanding of the potential benefits of mentoring and creating a support system. Written by Debra M. Barry, Heather Nesbitt, and Heather McAuslane, and published by the UF/IFAS Department of Agricultural Education and Communication, May 2024.